2022
DOI: 10.3390/su14127165
|View full text |Cite
|
Sign up to set email alerts
|

Travel Motivation during COVID-19: A Case from Nepal

Abstract: The tourism industry is one of the most affected industries by the COVID-19 pandemic. Understanding travel motivation is necessary for the tourism movement, even in the COVID-19 pandemic. Thus, this quantitative study aimed to explore travel motivation and its determinants. We collected 181 samples through a web-based questionnaire survey of the Nepali people in January and February 2021. The data were analyzed using a probit regression model through two different travel companion perspectives, i.e., traveling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Th is clarifi es that the bus was the primary mode of travel. A similar result was explored in Nepal, where people use coaches to travel during COVID-19 because it is cheaper and easy to travel in a group (Bhatta et al, 2022). Th e organizing trips show the current trends and expectations of travelers.…”
Section: Manners Of Spending Leisure Time By Peoplementioning
confidence: 56%
See 1 more Smart Citation
“…Th is clarifi es that the bus was the primary mode of travel. A similar result was explored in Nepal, where people use coaches to travel during COVID-19 because it is cheaper and easy to travel in a group (Bhatta et al, 2022). Th e organizing trips show the current trends and expectations of travelers.…”
Section: Manners Of Spending Leisure Time By Peoplementioning
confidence: 56%
“…Secondary and more-educated people majorly participated in the survey. During the online SNSs surveys, young and educated participants were frequently observed more than any others (Bhatta et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the novel predicting variables, it may be necessary to uncover additional variables that could predict motivation to travel during risky times, as well as to forecast trip satisfaction and intention to travel in the future. Other variables such as solo travel, group travel with friends or family members, travel mode, destination preferences and travel duration (Bhatta et al , 2022) could impact motivation to travel during a pandemic and may have an influence on satisfaction and intention for future travel during risky times.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies talk about the pandemic as having wonderful scope towards sustainable global economic regeneration, where it was discussed that the frequent lockdown and an on-and-off market have shown a direct impact on the global market; however, some recovery models based on reinvention of tourism-services-providing sectors worked as an opportunity towards rethinking from traditional set-up to upgraded initiatives for sustainable tourism [30][31][32]. Consecutively, Bhatta [33] also suggested that COVID-19 is a motivational tool to restructure the travel and tourism services, providing sectors in post-recovery destination-based tourism and providing a low-risk travel environment.…”
Section: Literature Reviewmentioning
confidence: 99%